2010
DOI: 10.1002/ange.201004929
|View full text |Cite
|
Sign up to set email alerts
|

Layer‐by‐Layer Films of Graphene and Ionic Liquids for Highly Selective Gas Sensing

Abstract: The best of both worlds: Graphene/ionic liquid (G–IL) layered films were obtained by direct reduction of graphene oxide in the presence of ionic liquids, followed by reassembly through electrostatic layer‐by‐layer (LbL) adsorption (see picture). The layer spacing of the graphene sheets is regularly expanded upon insertion of ionic liquid molecules (green discs). Selective sensing of aromatic compounds (red spheres) by using the G–IL LbL films was also achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
37
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(39 citation statements)
references
References 38 publications
1
37
0
1
Order By: Relevance
“…In another approach, self‐assembly of organic molecular‐functionalized graphene films has been utilized to construct gas/vapor detectors. Ji et al reported a VOC sensor fabricated by layer‐by‐layer assembly of graphene–ionic liquids (G‐ILs) on a quartz crystal microbalance. The decrease in frequency shifts, caused by gas adsorption, for single adsorption steps corresponds to the adsorption of the single G‐IL composite layer.…”
Section: Graphene Assemblies For Gas and Vapor Sensorsmentioning
confidence: 99%
“…In another approach, self‐assembly of organic molecular‐functionalized graphene films has been utilized to construct gas/vapor detectors. Ji et al reported a VOC sensor fabricated by layer‐by‐layer assembly of graphene–ionic liquids (G‐ILs) on a quartz crystal microbalance. The decrease in frequency shifts, caused by gas adsorption, for single adsorption steps corresponds to the adsorption of the single G‐IL composite layer.…”
Section: Graphene Assemblies For Gas and Vapor Sensorsmentioning
confidence: 99%
“…Several recent studies have reported that the incorporation of nanocrystals/nanoparticles in graphene-based gas sensors could improve sensor performance in terms of the sensitivity/detection limit, response time, or recovery time161718. In addition, several other groups have demonstrated that reduced graphene oxide (rGO) can act as a gas/vapour sensor with promising results111219202122. However, at present there have been no reports demonstrating selectivity using graphene and rGO in gas sensors.…”
mentioning
confidence: 99%
“…Recently, graphene has attracted much attention due to its unique single atom-layer structure, which contributes to its wide applications [26] in nanoelectronics, sensing devices, energy storage, and even tissue engineering. For example, graphene has proven to be a promising biocompatible scaffold that could accelerate the specific differentiation of human mesenchymal stem cells (hMSCs) into bone cells.…”
mentioning
confidence: 99%